Spinoza: a genealogy of civils rights - Durán Forero, Rosalba (Estudios de Filosofía, 1993)
Nine concepts elaborated in Spinoza’ s political thinking are considered anew. These, prior to human rights, would be part of a systematic construction of civil rights, having as their goal the realization of a true liberal democracy.